The Effect of Brain Gym on Grades 5-6 Students in Sd Negeri Kotalama 6 Malang City - Fitri Dian Rahmawati; Miftakhul Ulfa; Patemah Patemah (International Journal of Psychology and Mental Health, 2025)
Learning concentration is an important factor in educational success. However, students in grades 5-6 of SD Negeri Kotalama 6 Malang City have difficulty concentrating due to internal (motivation) and external (noise) factors. The main objective of this research is to investigate how brain exercises can impact the focus of students during their learning. The research employed a quasi-experimental method known as One Group Pre-test and Post-test Design. A specific group of 49 students was chosen intentionally for the study. The students' level of concentration was assessed using the Army Alpha Test both before and after they participated in brain exercises for five days, with each session lasting for 10 minutes. The data collected was analysed using the Wilcoxon Signed Rank Test. The findings revealed a notable improvement in the students' learning concentration, with a statistically significant increase (p = 0.000 < 0.05). Before the treatment, the majority of students had low concentration, while after the intervention, most showed moderate to high concentration. The conclusion of this study is that brain exercises are effective in improving students' learning concentration and are recommended to be implemented routinely in schools.